Letramentos na cultura digital e os efeitos da plataformização da leitura: experiência estética e performances textuais na recepção de Memórias póstumas de Brás Cubas na plataforma Skoob - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
This dissertation, developed within the Interdisciplinary Graduate Program in Education, Language and Technologies at the State University of Goiás, is linked to the research line “Language and Social Practices” and the axis “Language, Arts and Digital Culture,” and seeks to answer the following question: how do the discursive practices of readers on the Skoob Platform, related to the work Memórias Póstumas de Brás Cubas by Machado de Assis, reveal contemporary modes of literary reception mediated by Digital Culture? Throughout the investigation, the study sought to understand whether such practices contribute to the formation of critical readers or reproduce the immediatist and performative dynamics of platformization. Thus, the general objective of this study is to analyze digital literary literacy practices on the Skoob Platform based on reviews of Machado de Assis's work, considering aesthetic experiences and textual performances in the digital context. The theoretical framework is grounded in literacy studies as social practice (Street, 2014; Kleiman, 2014; Soares, 2002, 2017), literary literacy (Cosson, 2015, 2021; Paulino, 2001, 2004), Digital Culture (Santaella, 2013; Santaella and Kaufman, 2024), multiliteracies (Ribeiro, 2020; Rojo; Moura, 2019), and dialogism (Bakhtin, 1997). Methodologically, the research adopts a qualitative, exploratory, and descriptive-interpretive approach, using netnography (Kozinets, 2014) as an investigative strategy. The corpus consists of reviews published on the Skoob Platform between 2009 and 2025, selected through intentional criteria that consider textual length, language used, references to viralization, and publication temporality. The analysis revealed heterogeneity in digital literary literacy practices, evidencing both critical appropriations of the work and performative readings. The results demonstrate that the 2024 viralization expanded access to the work without necessarily guaranteeing critical appropriation, confirming that Digital Culture constitutes an ambivalent space for reader formation, enhancing cultural democratization while presenting risks of the aesthetic experience becoming superficial
Literacies in digital culture and the effects of platformization of reading: Aesthetic Experience and Textual Performances in the Reception of The Posthumous Memoirs of Brás Cubas on the Skoob Platform
Keywords: Letramento Literário Digital - Plataforma Skoob - Machado de Assis; Cultura Digital; Digital Literary Literacy - Skoob Platform - Machado de Assis; Digital Culture; LETRAS::LITERATURA BRASILEIRA